PENGARUH MINAT INDIVIDU TERHADAP PENGGUNAAN MOBILE BANKING: MODEL KOMBINASI TECHNOLOGY ACCEPTANCE MODEL (TAM) DAN THEORY OF PLANNED BEHAVIOR (TPB) - Suci Sulistiyarini (Jurnal Ilmiah Mahasiswa FEB, 2012)
This research has a purpose to examine the determinant of individual intention to use mobile banking. The antecedent of individual intention to use mobile banking in this research are perceived usefulness, perceived ease to use, attitude, subjective norm, and perceived behavioral control. This research is a development of previous research that uses a combination of TAM and TPB models in the development. Data collection method used is survey method by distributing 300 questionnaire. Respondents who becomes the object of this research were the city of Malang residents who use mobile banking facility from Bank Mandiri Tbk and BCA Tbk. A number of 109 questionnaires have been received back, can be used and can be processed using SmartPLS version 2.0 M3 software. The result showed that perceived usefulness and perceived ease of use affect an individual attitude using mobile banking. Attitude and subjective norm affect an individual intention using mobile banking, perceived behavioral control doesn’t affect an individual intention using mobile banking. The implications of this research are relevant for banking institutions to consider the factors which influence an individual intention to use mobile banking in the development the information systems. Keywords: Mobile banking, Perceived Usefulness, Perceived Ease of Use, Attitude, Subjective Norm, Perceived Behavioral Control, TAM and TPB.